assume that p and q are false, with r true. find the truth value for each statement r→(p∧~q), (p→q)∧(r→q) ~(pvq) pv~q
To me, the easiest way to do this is to convert each of these to English. if r then (p and not q). Since r is true, the result is (p and not q). Since p is false, the result is false, because for AND, if either side is false they both are. (if p then q) and (if r then q) Since p is false, the if p then q is false. Since this is an and, if the first part is false, the entire thing is false. Does this help with the others?
Join our real-time social learning platform and learn together with your friends!